2021
DOI: 10.1183/23120541.00190-2021
|View full text |Cite
|
Sign up to set email alerts
|

Impact of prior smoking exposure and COPD comorbidity on treatment response to monoclonal antibodies in patients with severe asthma

Abstract: Despite the prognostic role of smoking in asthma [1], clinical studies of asthma usually exclude current smokers or ex-smokers with a smoking history of >10 pack-years [2–5]. Specifically, the role of humanised monoclonal antibody therapy in patients with severe asthma and prior smoking exposure has not been studied; however, these drugs are used in patients with severe asthma and a history of smoking [6–9]. The aim of the present study was to evaluate in a real-world setting how a history of smoking and comor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“… 16 A single-center, observational cohort study from Germany found that antibody treatments (including mepolizumab), when added to standard asthma therapies, were as efficacious in ex-smokers suffering from severe asthma as they are in nonsmokers, by improving the asthma control, exacerbation rate and lung function of these patients. 37 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 16 A single-center, observational cohort study from Germany found that antibody treatments (including mepolizumab), when added to standard asthma therapies, were as efficacious in ex-smokers suffering from severe asthma as they are in nonsmokers, by improving the asthma control, exacerbation rate and lung function of these patients. 37 …”
Section: Discussionmentioning
confidence: 99%
“…16 A single-center, observational cohort study from Germany found that antibody treatments (including mepolizumab), when added to standard asthma therapies, were as efficacious in ex-smokers suffering from severe asthma as they are in nonsmokers, by improving the asthma control, exacerbation rate and lung function of these patients. 37 Evaluations from a number of other real-world databases also underscore the importance of everyday clinical experience with mepolizumab. The findings provide efficacy results that are similar to the GAN data and the results from controlled clinical trials.…”
mentioning
confidence: 99%
“…Our study results confirm recent findings by M orobeid et al . [ 30 ] analysing antibody treatment in patients with allergic or eosinophilic asthma and a smoking status of >10 PY, showing treatment efficacy of IL-5 antibodies. In contrast to our study only limited information concerning patient characteristics were provided, not allowing further phenotyping of patients.…”
Section: Discussionmentioning
confidence: 99%